Strategy Implementation and Success Factors of Koi Fish Marketing through Online Media at the Fara Koi Magetan Business Unit - Jefri Putri Nugraha; Dimas Bayu Sasongko (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze the marketing strategy of koi fish in ulate a marketing strategy using the koi fish marketing mix. Fara Koi Business Unit Farm and form The method used in this research is the descriptive method. The location of the research was done at Fara Koi Business Unit Farm, Sumberdodol Village, District of Panekan, Magetan Regency. The results showed that Fara Koi Business Unit Farm has implemented a marketing mix strategy well, each variable can be explained in detail. In products, the business unit has implemented product quality dimensions well, such as guaranteed fish quality, varied types, and sizes of koi fish, and product guarantees, as well as service or service. The price set by the business unit is lower than that of koi fish of the same quality on the market. The business unit's current target consumers are resellers, hobbies, and plasma farmers. Each target has a different price of each. There are two distribution channels carried out by the business unit, namely direct and indirect. The location of the business unit is not strategic. Promotions that have been carried out by the business unit have three aspects, namely advertising, sales promotion, and personal selling. Meanwhile, for each strategy made in between, namely, the addition of production capacity to meet consumer needs. Discounts for repeat customers. Promotion optimization by creating a special promotion division in the business unit organization